2004
DOI: 10.1002/hipo.20012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of theta power in hippocampal EEG during bar pressing and running behavior in rats during distinct behavioral contexts

Abstract: These experiments examine changes in theta power as measured by wavelet analysis in five rats performing a conditional visual discrimination task and a simple running task. In the conditional task, rats were trained to press one lever to initiate a trial and then to press one of two choice levers, each corresponding to one of two cue lights. Analysis of theta power in this operant task found a large decrease in theta power during the choice bar presses, in contrast to the increase in theta power during trial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 40 publications
7
59
0
Order By: Relevance
“…Theta power has been associated with sensorimotor processes (7), and one recent study has shown a dramatic decrease in theta power in the CA1 subfield associated with lever pressing for a reward (34). Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Theta power has been associated with sensorimotor processes (7), and one recent study has shown a dramatic decrease in theta power in the CA1 subfield associated with lever pressing for a reward (34). Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We have currently no explanation for this effect which, although significant, was not very marked. This might be due to the fact that theta oscillations are usually associated more with the intention than with the movement itself (Whishaw and Vanderwolf, 1973;Wyble et al, 2004), and that the rise of theta power precedes the onset of voluntary locomotion (Vanderwolf, 1969). We noticed that animals in the saline, cocaine and quinpirole+ cocaine groups exhibit closely spaced successive locomotory episodes.…”
Section: Drug Effects On the Power Of Theta Oscillationsmentioning
confidence: 93%
“…This could be due to theta rhythm oscillations being shut down when the rat stops at a reward location. The theta rhythm shows reductions at reward locations and decreases even as the rat is approaching a reward location (Wyble et al 2004). The temporary decrease in theta rhythm could result in periodicity being dependent on the latest reward location.…”
Section: Reward/stopping Locations Influence Context-dependent Firingmentioning
confidence: 99%
“…The temporary decrease in theta rhythm could result in periodicity being dependent on the latest reward location. Note that stopping per se does not have to reset the theta rhythm, as stopping at non-reward locations causes less suppression of theta rhythm (Wyble et al 2004). …”
Section: Reward/stopping Locations Influence Context-dependent Firingmentioning
confidence: 99%